2021
DOI: 10.3389/fpubh.2021.720761
|View full text |Cite
|
Sign up to set email alerts
|

Operationalization of One Health Burnout Prevention and Recovery: Participatory Action Research-Design of Nature-Based Health Promotion Interventions for Employees

Abstract: Burnout is, besides a global, complex phenomenon, a public health issue with negative consequences on personal, organizational, social, and economic levels. This paper outlines the co-design of a novel Nature-based Burnout Coaching intervention, called NABUCO. Due to the complexity of burnout, we propose a One Health approach in healthcare, educational and governmental pilot organizations, to deliver guidelines and protocols for prevention and recovery of burnout. We advocate the inclusion of the salutogenic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Our study resulted in an overview of several identified quality criteria to be considered when designing and implementing NBI in healthcare facilities ( Figure 2 ) and led us to a preliminary NBI-quality criteria framework ( Figure 3 ). The use of quality criteria supports the development of equitable, safe and adaptive protocols during implementation, as observed in studies proposing NBIs in an organizational setting ( 54 ).…”
Section: Discussionmentioning
confidence: 72%
“…Our study resulted in an overview of several identified quality criteria to be considered when designing and implementing NBI in healthcare facilities ( Figure 2 ) and led us to a preliminary NBI-quality criteria framework ( Figure 3 ). The use of quality criteria supports the development of equitable, safe and adaptive protocols during implementation, as observed in studies proposing NBIs in an organizational setting ( 54 ).…”
Section: Discussionmentioning
confidence: 72%
“…This collaboration takes into account the importance of creating a common language and terminology and understanding, while including patients’ perspectives. These efforts aim to bridge the gaps between the different stakeholders involved ( 4 , 52 ). Furthermore, our study shows that systematic monitoring and evaluation of the intervention process and iNBI impacts on biodiversity and health remains challenging.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, the recent study by Sterckx et al [ 70 ] has proposed a One Health-based protocol for the holistic management of burnout syndrome. Interestingly, the authors emphasized the strict relationship between mind, body, and emotions within the individuals, integrating the patient in a broader context, including both social and environmental factors.…”
Section: One Health Approachmentioning
confidence: 99%